On the choice of the phase difference increment in radiofrequency-spoiled gradient-echo magnetic resonance imaging of liquids with consideration of diffusion - Jochen Leupold; Matthias Weigel; Sébastien Bär (PLoS ONE, 2025)
In magnetic resonance imaging, the radiofrequency-spoiled gradient-echo method aims for fast acquisition of T1-weighted images. The spoiling mechanism is driven by the radiofrequency phase difference increment. In clinical (in-vivo) imaging, the phase difference increments of 50°, 115.4°, 117° and 150° are in standard use. In this work, we examine how accurate these increments guarantee T1-weighting also in free liquids, in particular with different diffusion coefficients. The non-standard phase difference increment 169°, which was shown to improve T1 quantification methods, is considered as well. Signal simulations were performed with the extended phase-graph with diffusion concept; experiments were performed on different liquid phantoms (water with contrast medium, silicone oil). In the simulations, a parameter space consisting of relaxation times, diffusion coefficient, sequence repetition time, flip angle and image resolution was examined. The resulting efficiency of radiofrequency spoiling was quantified by the average deviation of the simulated signal-vs-flipangle curve from the ideal curve. It was found that ideal spoiling is generally better approximated with a phase difference increment of 169° compared to the other examined values. From the four commonly used values, 115.4° is recommended, in particular when the influence of diffusion is low. For clinical in-vivo imaging parameters, all examined values of the phase difference increments offer a good approximation of ideal spoiling as expected. In conclusion, radiofrequency spoiling in free liquids can be improved by using a phase difference increment of 169°.